Medical and patient attitude towards vaginal atrophy: the AGATA study. (1st November 2016) - Palma, F.; Della Vecchia, E.; Cagnacci, A.; ,
Abstract: Objectives: To provide data on current management of vaginal atrophy (VA) in a nationwide setting. Methods: A cross-sectional, multicenter study was made in 913 postmenopausal women consulting 22 gynecological outpatient services. VA was diagnosed with a combination of subjective symptoms and objective evaluations. Women with a previous diagnosis and those with a new diagnosis of VA filled additional questionnaires regarding modalities of VA management and reasons for missing diagnosis, respectively. Results: 730/913 (80%) women had ever had a diagnosis of VA. In 274 (37.5%), the diagnosis was made prior to, and in 456 (62.5%) during the investigation. Of women with a new VA diagnosis, 81.1% had never discussed their symptoms with the health-care practitioner (HCP), and 78.7% ( n = 359) had never been questioned by an HCP. Of women with a previous VA diagnosis, 90.2% had been treated with systemic (10.1%), local hormonal (49.4%) or local non-hormonal (30.5%) therapy. At the time of investigation, 61.9% of these women had stopped treatment, with only 3.3% having been successfully cured. Conclusions: VA is highly prevalent in postmenopausal women. Its current management and treatment seem to be highly unsatisfactory and can be improved by medical sensitization and patient education.